2016
DOI: 10.1007/s11356-016-8211-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-based detection of potentially pathogenic bacteria in membrane bioreactor (MBR) systems treating municipal wastewater: a case study

Abstract: Although membrane bioreactor (MBR) systems provide better removal of pathogens compared to conventional activated sludge processes, they do not achieve total log removal. The present study examines two MBR systems treating municipal wastewater, one a full-scale MBR plant and the other a lab-scale anaerobic MBR. Both of these systems were operated using microfiltration (MF) polymeric membranes. High-throughput sequencing and digital PCR quantification were utilized to monitor the log removal values (LRVs) of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 60 publications
3
28
0
Order By: Relevance
“…The 16S rRNA gene copy log removal was consistent with bacterial removal via anaerobic digestion as reviewed by Avery et al 57 and an AnMBR operated at 35°C that also demonstrated a 3-log reduction in total bacteria copy numbers. 58 Changes in abundance of the ARGs and intI1 normalized to 16S rRNA gene copies (Fig. 4) showed no significant difference (ANOVAs, p > 0.85) suggesting no selective removal of any specific gene over another gene.…”
Section: Enumeration Of 16s Rrna Genesmentioning
confidence: 90%
See 1 more Smart Citation
“…The 16S rRNA gene copy log removal was consistent with bacterial removal via anaerobic digestion as reviewed by Avery et al 57 and an AnMBR operated at 35°C that also demonstrated a 3-log reduction in total bacteria copy numbers. 58 Changes in abundance of the ARGs and intI1 normalized to 16S rRNA gene copies (Fig. 4) showed no significant difference (ANOVAs, p > 0.85) suggesting no selective removal of any specific gene over another gene.…”
Section: Enumeration Of 16s Rrna Genesmentioning
confidence: 90%
“…These results are consistent with previous observations by Harb and Hong who reported distinct communities within the influent and effluent from an AnMBR operated at 35°C treating real wastewater. 58 Significant differences ( p < 0.01) in dominant genera between membrane feed and membrane final filtrate were determined by DESeq (Fig. 7).…”
Section: Enumeration Of 16s Rrna Genesmentioning
confidence: 99%
“…Furthermore, the lower LRV for E. coli seen in this study as compared to a similar AAO MBR, which was examined using culture-based methods [122], illustrates the potential for disparities in results obtained by different detection techniques. Another recent work also employed quantitative digital PCR for the detection of pathogenic bacteria in both a full-scale aerobic MBR and a lab-scale anaerobic MBR treating the same municipal wastewater [123]. Results of the same study targeting total bacteria, Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae showed LRVs of 4.1, 2.7, 1.0, and 3.1, respectively, in the aerobic MBR system and 3.1, 4.2, 1.2, and 3.9, respectively, in the anaerobic MBR [123].…”
Section: Pathogen-associated Risk Reduction By Membrane Bioreactorsmentioning
confidence: 99%
“…Another recent work also employed quantitative digital PCR for the detection of pathogenic bacteria in both a full-scale aerobic MBR and a lab-scale anaerobic MBR treating the same municipal wastewater [123]. Results of the same study targeting total bacteria, Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae showed LRVs of 4.1, 2.7, 1.0, and 3.1, respectively, in the aerobic MBR system and 3.1, 4.2, 1.2, and 3.9, respectively, in the anaerobic MBR [123]. In addition to reiterating the potential for variability among pathogenic species, these results also accentuate the potential for improved pathogen removal rates by anaerobic MBRs.…”
Section: Pathogen-associated Risk Reduction By Membrane Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation